MODEL MATEMATIKA KADAR AIR KESEIMBANGAN DUA PARAMETER UNTUK LADA - Somantri, Agus Supriatna (Pusat Penelitian dan Pengembangan Perkebunan, 2003)
The Mathematical Model for Two Parameters of Equilibrium Moisture Content for Black PepperEquilibrium of Moisture Content (EMC) plays an important role in drying and storage processes. The research was conducted at the Post Harvest Laboratory, Research Institute for Spices and Medicinal Crops, from June 2 to 30, 2001. The research aimed to determine a suitable model of isotherm sorption for pepper commodities, which can be applied on drying and storage processes at the field. The method used was the static method at temperature 40, 45 and 50 oC and range of water activity (Aw) 0.20 â€“ 0.64. The models correlated were the Henderson, Chung-Pfost, Oswin and Halsey, by using numerical method with the BASIC language. The result showed that the two parameters (temperature and relative humidity) of mathematical model had given good result compared with the experimental data. The model of Halsey showed the best accuracy among the other models and it can be used for prediction of the isotherm sorption for black pepper, while the Oswin model for white pepper.Â